Perception and Experience of Student-Facilitated Problem-Based Learning in Medical Education: A Qualitative Analysis in a Resource-Limited Setting of Nepal - Joshi , Lok Raj; Nembang, Penchha; Hamal, Deependra; Thakur , Chandan; Anu , Anuraj; Bista, Binamra (Europasian Journal of Medical Sciences, 2024)
Background: Shortage of trained faculty to facilitate problem-based learning (PBL) is a major challenge in resource-limited settings. Our study aimed to assess the effectiveness and shortcomings of student-facilitated PBL in such a setting in Nepal. Methods: First year and second year medical students (80 students) conducted student-facilitated PBL modules in Karnali Academy of Health Science, Jumla during March and April of 2024. This report presents the retrospective reflexive thematic analysis of the perceptions or experiences of the students and faculty involved in the PBL modules. The data comprised of presentation slides of six teams of student during wrap-up seminars and notes taken during four focus group discussions (25 participants in total) of the students and faculty members after the PBL modules. Results: The major themes included prior concerns and overall experience, facilitator and facilitation-related experience, group dynamics, learning experience, resource management and suggestions for training. Most of the students and faculty valued the student-facilitated PBL modules positively. More self-directed nature, in-depth study, hesitation-free discussions and development of problem-solving and leadership skills were among the perceived advantages of the PBL modules. Major challenges were related to inadequacy of the PBL process skills, team management and time management issues. Further training of students in those areas was suggested. Conclusions: The overall experience of the students and faculty members remained positive. Thus, student-facilitated PBL modules with the provision of faculty supervision and adequate training of students may serve as an alternative model of PBL in resource-limited scenarios.